„Parcite autem obsecro Lampridio Vestro in Zabanio redivivo, Dynastae spectatissimi…”: Apafi Mihály temetésének gyászbeszédei és a szász Zabanius Izsák latin orációja - Mikó, Gyula (Studia Litteraria, 2013)
Izsák Zabanius, rector (school teacher) of Szeben (Hermannstadt) told his Latin sermon on the funeral of Mihály Apafi, Duke of Transylvania. During his reign, Apafi succeeded in expelling the Hapsburgs and the Turkish from the territory of Hungary and Transylvania, so after the death of the duke, Transylvania was soon under the rule of Emperor Leopold I. This paper presents the way the leaders of Transylvania and especially the Saxons regulated by the new interests of the Western ruler, and how they immediately turned from a tradition of one and a half century.